2014
DOI: 10.14419/ijbr.v2i2.3592
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobinuria due to hypophosphataemia in last trimester pregnant buffalo

Abstract: A buffalo in her last trimester pregnancy was referred to clinic with signs of anorexia, voiding dark red coloured urine, dullness, mild diarrhoea and depression. It was diagnosed as an acute case of parturient haemoglobinuria by assessing the serum biochemical parameters. It had low levels of serum protein, albumin and phosphorous. Haemogram revealed decreased erythrocyte count, haemoglobin and haematocrit. The buffalo had been treated with phosphorous supplements and other supportive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Circulating oxidants have also caused erythrocyte damage in hypophosphatemic dairy cows (Jubb et al, 1990). Almost all cows develop hemoglobinuria two to four weeks after calving (Radostits et al 2007), whereas buffalos develop hemoglobinuria before or after parturition (Pirzada and Hussain, 1998;Reddy et al, 2014). In the current report, hemoglobinuria was detected 1-2 weeks after lambing.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating oxidants have also caused erythrocyte damage in hypophosphatemic dairy cows (Jubb et al, 1990). Almost all cows develop hemoglobinuria two to four weeks after calving (Radostits et al 2007), whereas buffalos develop hemoglobinuria before or after parturition (Pirzada and Hussain, 1998;Reddy et al, 2014). In the current report, hemoglobinuria was detected 1-2 weeks after lambing.…”
Section: Discussionmentioning
confidence: 99%
“…The urine of PPH affected animals are 100% positive for hemoglobinuria and 95% positive for albuminuria [35]. Some researchers [10] [36] [38] have been reported the presence of protein, and high PH (pH of 8.0 -9.0) in the PPH affected animals. Akhtar et al [35] and Soren et al [23] reported that the microscopic examinations have been confirmed the presence of erythrocyte in urine with uniformly radish brown color [10].…”
Section: Urine Analysismentioning
confidence: 99%
“…Copper depletion also cause oxidative trauma to RBCs which is associated with consumption of cruciferous plants, dietary phosphorous insufficiency, and saponin from berseem (Brechbühl et al 2008;Neto et al 2007). This is a critical disease condition with accompanying hypophosphatemia is described by intravascular hemolysis and anemia with potentially lethal results (Durrani et al 2010; Reddy et al 2014). A possible indicator of the bioavailability of feed phosphorus in dairy cows is the plasma inorganic phosphatelevel (Montiel et al 2007) and hemoglobin level to assess the presence of anemia (Turgut 2000).…”
Section: Introductionmentioning
confidence: 99%